Biochemical mechanisms underlying the pro-apoptotic activity of 7,8-dihydroxy-4-methylcoumarin in human leukemic cells - Riveiro, Maria Eugenia (2008)
The search for new drugs requires a deep understanding of the molecular basis of drug action, being necessary the elucidation of the mechanism of action with the understanding of the relationship between structure and activity. In the present study, we evaluated the pro-apoptotic activity of 7,8-dihydroxy-4-methylcoumarin (DHMC) and its underlying mechanisms in human leukemic cells. Here, we present evidence that DHMC induced selective and concentration-dependent apoptosis in human leukemic cells. The pro-apoptotic effect of DHMC was mediated by activation of the JNKs and inhibition of the ERK1/2 and PI3K/Akt pathways, with no participation of the p38 cascade after 24h of treatment. Indeed, down-regulation of the proto-oncogene c-myc as well as induction of the cell cycle inhibitor p21(WAF1/CIP1) through a p53 independent mechanism were observed in U-937 cells. These findings suggest that DHCM may have a potential therapeutic role in the future treatment of hematological malignancies.